Buying and Selling Fertilizer in Agriculture: Study of Takhrij and Syarah Hadith on Agrotechnology - Iwan Iwan; Ninit Kurnia; Tuti Garnasih; Kifah Gibraltar Bey Fananie (Gunung Djati Conference Series, 2021)
The purpose of this study is to discuss the hadith of the Prophet Muhammad about buying and selling fertilizers. The research method used in this study is a qualitative method through the approach of takhrij and syarah hadith agrotechnology. The results and discussion of this study are the buying and selling activities of fertilizers recommended by the Prophet Muhammad, and are still developing in modern times. The conclusion of this study is that the buying and selling of fertilizers was recommended by the Prophet Muhammad and also has many other benefits.